Urban areas parameterisation for CFD simulation and cities air quality analysis. (15th January 2020) - Badas, Maria Grazia; Salvadori, Luca; Garau, Michela; Querzoli, Giorgio; Ferrari, Simone
The aim of this work is to highlight the importance of a site-specific characterisation of urban areas needed for computational fluid dynamics (CFD) simulations and urban air quality studies. As a case study, we consider Cagliari, an Italian town, whose heterogeneous urban texture can be representative of many European historical towns, quite different from large American cities that are generally analysed in literature. Basic steps needed to compute the main morphometric and fluid dynamics parameters from digital elevation models (DEM) are reviewed and some possible caveats on using gridded DEM analysis are highlighted. Results show how site-specific analysis provides quite different parametrisations from those obtained by literature results, which cannot be transposed to other urban contexts. Morphometric site-specific analysis represents a key issue in urban numerical simulations, since the application of non-representative morphometric input data may dramatically affect their results.